2010
DOI: 10.1158/0008-5472.can-10-1545
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Splicing of Caspase 9 Is Modulated by the Phosphoinositide 3-Kinase/Akt Pathway via Phosphorylation of SRp30a

Abstract: Increasing evidence points to the functional importance of alternative splice variations in cancer pathophysiology. Two splice variants are derived from the CASP9 gene via the inclusion (Casp9a) or exclusion (Casp9b) of a four-exon cassette. Here we show that alternative splicing of Casp9 is dysregulated in non-small cell lung cancers (NSCLC) regardless of their pathologic classification. Based on these findings we hypothesized that survival pathways activated by oncogenic mutation regulated this mechanism. In… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
109
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(115 citation statements)
references
References 44 publications
6
109
0
Order By: Relevance
“…Therefore, we hypothesized that phosphorylation events might impact the association between hnRNP U and C9/E3. Nevertheless, our findings in this study demonstrate that phosphorylation of hnRNP U is unlikely to play a role, and the regulatory mechanism is mainly via phosphorylation of hnRNP L. Together with the findings that caspase-9a/9b ratio is higher in nontransformed than in transformed cells (4,5) and the enhanced association of hnRNP U in nontransformed cells, these data extend the mechanistic insights into the dysregulation of caspase-9 splicing in transformed cells. In this paradigm, certain survival/oncogenic kinases are activated and phosphorylate hnRNP L in transformed cells.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Therefore, we hypothesized that phosphorylation events might impact the association between hnRNP U and C9/E3. Nevertheless, our findings in this study demonstrate that phosphorylation of hnRNP U is unlikely to play a role, and the regulatory mechanism is mainly via phosphorylation of hnRNP L. Together with the findings that caspase-9a/9b ratio is higher in nontransformed than in transformed cells (4,5) and the enhanced association of hnRNP U in nontransformed cells, these data extend the mechanistic insights into the dysregulation of caspase-9 splicing in transformed cells. In this paradigm, certain survival/oncogenic kinases are activated and phosphorylate hnRNP L in transformed cells.…”
Section: Discussionsupporting
confidence: 69%
“…The ratio of caspase-9a/9b isoform is dysregulated in nonsmall cell lung cancer (NSCLC) 2 cells (4,5), and the factors implicated in regulating the alternative splicing of caspase-9 include endogenous ceramides (6), SRSF1 (SRp30a or ASF/SF2) (5,7,8), and heterogeneous nuclear ribonucleoprotein L (hnRNP L) (4). De novo ceramide synthesis and SRSF1 have been documented to down-regulate the level of caspase-9b mRNA in contrast to hnRNP L, which represses the inclusion of four-exon cassette to favor the formation of caspase-9b.…”
mentioning
confidence: 99%
“…Importantly, it appears that capsase-9a is proapoptotic, but the shorter isoform, caspase-9b, is antiapoptotic (Seol and Billiar 1999;Srinivasula et al 1999). Recently, Shultz and colleagues have found that this alternative splicing of caspase-9 is defective in nonsmall cell lung carcinoma (NSCLC) (Shultz et al 2010). Specifically, the authors showed that K-Ras12V overexpression increased the ratio of caspase-9a to capase-9b, while epidermal growth factor receptor (EGFR) overexpression lowered this ratio.…”
Section: Transcriptional Regulation Of Caspasesmentioning
confidence: 99%
“…Akt is activated by phosphoinositide-3-kinase (PI3K), and phosphorylates several distinct SR proteins such as SRp40 (Patel et al 2005) and SF2/ASF (White et al 2010) that ultimately regulate splicing events. For example, aberrant Akt signaling affects splicing of Casp9 in non-small cell lung cancers (Shultz et al 2010).…”
Section: Microenvironments Affecting Splicingmentioning
confidence: 99%